“They won’t prosecute, but they will though:” the continuing struggle between criminalization and harm reduction within the criminal justice system in the context of an opioid overdose crisis - Julia Dickson-Gomez; Sarah Krechel; Jessica Ohlrich; Jennifer Hernandez-Meier; Constance Kostelac (Harm Reduction Journal)
Abstract People who use drugs (PWUD) come into frequent contact with the police including after calling for emergency medical services when witnessing an opioid overdose. Good Samaritan laws have been passed in many jurisdictions to protect people from prosecution if they call for emergency services. Other interventions have used police to connect people to harm reduction and drug treatment services. In contrast, more traditional policing practices that criminalize drug use persist, potentially increasing overdose risk and decreasing the likelihood that PWUD will call 911 in the case of an overdose. Little research has examined how all these different and contradictory policies have been implemented in practice. This paper presents data from in-depth interviews with 66 PWUD about their overdose experiences. Interviews explored the context in which overdose occurred; what actions participants took when witnessing an overdose, including whether they administered naloxone or called 911; and if they called 911, what law enforcement and emergency medical services (EMS) offered or did upon arrival (e.g. offer naloxone, refer to treatment, arrest, or confiscate drugs). Participants reported frequently being arrested following overdoses as there were many exceptions to the Good Samaritan Law. While in prison or jail, participants were not provided MOUD or naloxone and many experienced an overdose while in custody or shortly upon release. Few participants reported receiving referrals to drug treatment or ham reduction, and many described law enforcement officers’ engaging in practices that discourage PWUD from calling 911.